Strategi Pengembangan Padi Inpari IR Nutrizinc di Kabupaten Pandeglang Provinsi Banten - Putu Surya Dhana; Achmad Tjachja Nugraha; Akhmad Mahbubi (SAFE-Network, 2026)
The government’s strategy to reduce the prevalence of stunting in Indonesia is to promote the cultivation of Inpari IR Nutrizinc rice, which has a high zinc content of 34.5 ppm. This study aims to analyze internal and external factors, develop alternative strategies, and determine priorities for the development of Inpari IR Nutrizinc rice. The study was conducted in Pandeglang Regency, Banten Province, involving 15 informants selected through purposive sampling. Data were collected via questionnaires, field observations, and interviews, then analyzed using the IFE, EFE, IE, SWOT, and QSPM matrices. The analysis results indicate that the internal conditions of the farming business fall into the “very strong” category (IFE score of 2.59). In contrast, the external conditions fall into the “very supportive” category (EFE score of 3.39). The combination of these scores places the farming business in Cell II of the IE matrix, with strong external conditions and average internal conditions; therefore, the appropriate strategy is aggressive marketing to capitalize on existing opportunities. The SWOT matrix evaluation yielded six alternative strategies, which were then ranked using the QSPM: Strategy C (7.12), D (6.39), B (6.18), A (6.12), E (6.12), and F (5.98). Strategy C branding healthy rice to support the stunting reduction program ranked highest and was designated as the priority strategy.